2008
DOI: 10.1007/s00467-008-0899-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil versus cyclosporine for remission maintenance in nephrotic syndrome

Abstract: We performed a multi-centre randomized controlled trial to compare the efficacy of mycophenolate mofetil (MMF) to that of cyclosporine A (CsA) in treating children with frequently relapsing nephrotic syndrome and biopsy-proven minimal change disease. Of the 31 randomized initially selected patients, seven were excluded. The remaining 24 children received either MMF 1200 mg/m 2 per day (n=12) or CsA 4-5 mg/kg per day (n=12) during a 12-month period. Of the 12 patients in the MMF group, two discontinued the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 34 publications
2
61
0
2
Order By: Relevance
“…Compared with calcineurin inhibitors such as cyclosporine A, MMF has a better side effect profile. Patients on MMF had better eGFR than those on cyclosporine A [7]. Hence, MMF would be a good alternative immunosuppressant, particularly in patients who had evidence of calcineurin inhibitor toxicity [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with calcineurin inhibitors such as cyclosporine A, MMF has a better side effect profile. Patients on MMF had better eGFR than those on cyclosporine A [7]. Hence, MMF would be a good alternative immunosuppressant, particularly in patients who had evidence of calcineurin inhibitor toxicity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently it was also reported in randomized studies to induce remission of proteinuria in IgA nephropathy [4,5], and achieve equivalent therapeutic efficacy when compared with standard Ponticelli regimen in idiopathic membranous nephropathy [6]. More recently, mycophenolate is reported to be a less toxic adjuvant agent for remission maintenance in childhood-onset relapsing or steroid-dependent MCD compared with cyclosporine [7][8][9]. In adults, mycophenolate is also shown to be a promising alternative treatment in a case series of 5 subjects [10].…”
Section: Introductionmentioning
confidence: 99%
“…As new treatments such as mycophenolate mofetil and rituximab become available (2,36,37), indications for follow-up renal biopsies aimed at detecting early signs of CsAN are rapidly decreasing. Nonetheless, our data suggest that if patients' disease is well controlled with low dosages of CsA and if they do not develop hypertension, then a renal biopsy can probably be postponed to after 4 to 5 yr of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies with limited statistical power have shown that MMF has steroid-sparing effects and reduces relapse rates in patients with FR-SSNS, albeit with varying efficacy. [11][12][13][14][15][16][17][18] We studied efficacy and safety of MMF in patients with FR-SSNS in comparison with CsA in a prospective randomized multicenter open-label crossover trial.…”
mentioning
confidence: 99%